Group Dynamics in Sports: An Overview and Recommendations on Diagnostic and Intervention - Kleinert, J.; Ohlert, J.; Carron, B.; Eys, M.; Feltz, D.; Harwood, C.; Linz, L.; Seiler, R.; Sulprizio, M. (The Sport Psychologist, 2012)
Working with teams and training groups is a common and major challenge for applied sport psychologists. This document is a position statement on the rationales, methods, and procedures of team-focused approaches in the practice of sport psychology. Furthermore, practice recommendations and research desiderata are discussed. To develop the paper, a consensus conference with nine experts from North America and Europe was held in Spring 2010. First, the paper presents the rationale for team-focused interventions and addresses the concepts of team cohesion, team efficacy, team potency, and a task involving leadership style. Second, the contributions of sport psychologists to enhancing group functioning are discussed, including methods for enhancing interpersonal skills, team climate, and coach athlete relationships. Third, determinants of how sport psychologists decide procedure and build trust in working with teams are articulated. Finally, the consensus group recommends an intensified effort to examine the effects and practice applicability of theory-driven, ecologically valid interventions.